You read French? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Access to French-language books is now much easier, thanks to the new Afrilivres Website set up by African publishers. You can even order and pay online.Website: www.afrilivres.com